Association between ambient temperature and humidity, vaginal temperature, and automatic activity monitoring on induced estrus in lactating cows - Polsky, Liam B.; Madureira, Augusto M. L. [UNESP]; Drago Filho, Eraldo L. [UNESP]; Soriano, Sergio; Sica, Alex. F.; Vasconcelos, Jose L. M. [UNESP]; Cerri, Ronaldo L. A. (Elsevier B.V., 2017)
The objective of this study was to determine the association between ambient temperature and humidity, vaginal temperature, and automated activity monitoring in synchronized cows. Lactating Holstein cows (n = 641; 41.5 +/- 9.4 kg of milk/d) were fitted with leg mounted pedometers, resulting in 843 evaluated activity episodes of estrus. Vaginal temperature was monitored using thermometers attached to an intravaginal device as part of a timed artificial insemination (TAI) protocol; vaginal temperature was recorded every 10 min for 3 d. Ambient temperature and relative humidity were monitored using an external thermometer placed in the center of each pen. Milk production and body condition score (BCS) data were collected at the time of thermometer insertion. All statistical analysis was performed in R (https://www.r-project.org/)using Pearson correlation, analysis of variance, and logistic regression. Heat stress was calculated based on the percentage of time the cow spent with a vaginal temperature >= 39.1 degrees C (PCT39) 9 to 11 d before TAI, and was classified as high (>= 22.9%) or low (<22.9%). The mean vaginal temperature was 38.9 +/- 0.2 degrees C, and the mean maximum and minimum vaginal temperatures were 39.7 +/- 0.5 degrees C and 38.0 +/- 0.8 degrees C, respectively, with an average amplitude of 1.71 +/- 0.9 degrees C. Mean relative increase (RI) of estrus walking activity was 237.0 +/- 160%. Animals with low BCS had a lower RI compared with cows with medium BCS (260.31 +/- 17.45% vs. 296.42 +/- 6.62%). Cows in early lactation showed lower RI compared with mid- and late -lactation animals (265.40 +/- 9.90% vs. 288.36 +/- 11.58% vs. 295.75 +/- 11.29% for early, mid, and late lactation, respectively). Temperature-humidity index (THI) conditions categorized as low (THI <65) were associated with greater RI compared with medium (>65 to <70) and high THI (>70). We detected no significant effect of PCT39 or milk production on RI, whereas parity exhibited a tendency. Cows that displayed greater RI at estrus had greater pregnancies per artificial insemination (P/AI) than cows with low RI (27 vs. 20%) or no RI (27 vs. 12%). Primiparous cows had greater P/AI than multiparous cows (27 vs. 20%), and cows in early and mid lactation had improved P/ AI than those in late lactation (26 vs. 22 vs. 16% for early, mid, and late lactation, respectively). An interaction was.observed between PCT39 and THI on P/AI, where a subpopulation of cows with high PCT39 had decreased P/AI under high THI conditions, but no differences in P/AI were observed for high PCT39 cows under medium or low THI conditions (13 vs. 24 vs. 26%). Future research should aim to refine variables related to hyperthermia and to understand the effects of body temperature on estrus expression and pregnancy rates.
Keywords: heat stress; automated activity monitoring; estrus activity